2019
DOI: 10.1111/ijcp.13352
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health (mHealth) technology for improved screening, patient involvement and optimising integrated care in atrial fibrillation: The mAFA (mAF‐App) II randomised trial

Abstract: Background Current management of patients with atrial fibrillation (AF) is limited by low detection of AF, non‐adherence to guidelines and lack of consideration of patient's preferences, thus highlighting the need for a holistic and integrated approach to AF management. This study aims to determine whether a mHealth technology‐supported AF integrated management strategy will reduce AF‐related adverse events. Methods/design The mAFA II trial is a prospective, cluster randomised controlled trial. The 40 sites wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 40 publications
0
92
0
2
Order By: Relevance
“…The design of Mobile health technology for improved screening, patient involvement, and optimizing integrated care in the Atrial Fibrillation (MAFA II) study program has been previously published [13]. Briefly, Huawei smart technology was used for screening of AF in the general population (referred to as the 'Huawei Heart Study'), and the identified AF patients were then transferred into a structured program of holistic and integrated care using a smartphone App (mAF App) [13].…”
Section: Methodsmentioning
confidence: 99%
“…The design of Mobile health technology for improved screening, patient involvement, and optimizing integrated care in the Atrial Fibrillation (MAFA II) study program has been previously published [13]. Briefly, Huawei smart technology was used for screening of AF in the general population (referred to as the 'Huawei Heart Study'), and the identified AF patients were then transferred into a structured program of holistic and integrated care using a smartphone App (mAF App) [13].…”
Section: Methodsmentioning
confidence: 99%
“…108 Subsequent to the Huawei Heart Study, mAFA II 109 was a cluster RCT to assess the impact of integrated care using a mobile AF application (mAFA) compared with usual care on clinical outcomes among 3,324 AFpatients with two or more stroke risk factors. 109 The trial demonstrated that rates of composite outcome (ischemic stroke/systemic thromboembolism, death, and rehospitalization) and rehospitalization were lower among mAFA patients vs the usual-care control group (1.9% vs 6.0%, HR 0.39, 95% CI 0.22-0.67 and 1.2% vs 4.5%, HR 0.32, 95% CI 0.17-0.60, respectively). 109 In an ancillary analysis of mAFAII, proactive assessment of bleeding risks using the HAS-BLED score resulted in mitigation of modifiable bleeding risk factors, fewer bleeding events and an increase in OAC uptake compared to usual care.…”
Section: Wearable Technologymentioning
confidence: 96%
“…109 The trial demonstrated that rates of composite outcome (ischemic stroke/systemic thromboembolism, death, and rehospitalization) and rehospitalization were lower among mAFA patients vs the usual-care control group (1.9% vs 6.0%, HR 0.39, 95% CI 0.22-0.67 and 1.2% vs 4.5%, HR 0.32, 95% CI 0.17-0.60, respectively). 109 In an ancillary analysis of mAFAII, proactive assessment of bleeding risks using the HAS-BLED score resulted in mitigation of modifiable bleeding risk factors, fewer bleeding events and an increase in OAC uptake compared to usual care. 110 Another approach was illustrated with the NOMED-AF (NCT03243474) study, 111 which assessed the prevalence of AF and concomitant comorbidities in a population aged ≥65 years.…”
Section: Wearable Technologymentioning
confidence: 96%
“…19 The Huawei Heart Study also showed the usefulness of photoplethysmographic (PPG) -based technology in population screening for AF, with the positive predictive value of PPG signals being 91.6% and leading to improved anticoagulation use (>80%). 20 Risk assessment continues to evolve, with availability of new data showing stroke risks associated with AF patients with hypertrophic cardiomyopathy 21 and imaging-documented significant coronary artery lesions. 22 There has been much interest into use of sophisticated methods such as machine-learning, even predicting incident AF from a simple 12-lead ECG.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…The ABC pathway approach has now been shown in independent studies to be associated with a reduction in mortality, hospitalization and adverse outcomes, as well as reduced healthcare costs, when compared to 'non-ABC' adherent management. [47][48][49][50] The ABC pathway was tested in a cluster randomized trial showing improved clinical outcomes with an ABC pathway management based on an interactive App that included risk assessments, patient decision aids, educational materials and dynamic tracking of risk (mAFA-II trial 20 ; presented as Late Breaking Science at the ESC congress, September 2019).…”
Section: Non-vitamin K Antagonist Oral Anticoagulants and Atrial Fibrmentioning
confidence: 99%